Avoiding Axillary Sentinel Lymph Node Biopsy after Neoadjuvant Systemic Therapy in Breast Cancer: Rationale for the Prospective, Multicentric EUBREAST-01 Trial - Reimer, Toralf (Cancers (Basel), 2020)
SIMPLE SUMMARY: Improvements in systemic treatments for breast cancer have increased the rates of pathologic complete response (pCR) in patients receiving preoperative systemic therapy (PST), offering the opportunity to de-escalate, and perhaps eliminate, surgery in patients who have a pCR. We propose a clinical trial in which only patients with the highest likelihood of having a pCR after PST will be included and type of surgery will be defined according to the response to PST rather than on the classical T (for tumor size in the breast) and N (for axillary lymph node involvement) status at presentation. In the planned trial, axillary surgery will be eliminated completely (no axillary sentinel lymph node biopsy) for initially clinical node-negative patients with radiologic complete remission and a breast pCR as determined in the lumpectomy specimen. ABSTRACT: Currently, axillary surgery for breast cancer is considered only as staging procedure, since the risk of developing metastasis depends on the biological behavior of the primary. The postsurgical therapy should be considered on the basis of biologic tumor characteristics rather than nodal involvement. Improvements in systemic treatments for breast cancer have increased the rates of pathologic complete response (pCR) in patients receiving neoadjuvant systemic therapy (NAST), offering the opportunity to de-escalate surgery in patients who have a pCR. European Breast Cancer Research Association of Surgical Trialists (EUBREAST)-01 is a clinical trial in which only patients with the highest likelihood of having a pCR after NAST (triple-negative or HER2-positive breast cancer) will be included and type of surgery will be defined according to the response to NAST rather than on the classical T (for tumor size in the breast) and N (for axillary lymph node involvement) status. In the discussed trial, axillary surgery will be eliminated completely (no axillary sentinel lymph node biopsy) for initially clinical node-negative (cN0) patients with radiologic complete remission and a breast pCR in the lumpectomy specimen. The trial design is a multicenter single-arm study with a limited number of patients (n = 267), which might give practice-changing results in a short period of time, sparing the time and the costs of a randomized comparison.